Bank selection criteria employed by undergraduates in a dual-banking environment / Wei-Loon Koe - Wei-Loon, Koe (Research Management Institute (RMI), 2012)
Banks are facing stiffer competition in today’s business world than in the past. As we know, customers are vital to the survival of banks. Thus, understanding of the criteria that are deemed to be important in choosing a bank is indeed crucial, especially in a dual-banking environment like Malaysia. However, research into bank selection criteria of specific customer segment still remains limited. As such, this study is carried out to identify the bank selection criteria employed by undergraduates choosing for conventional, Islamic and both types of banks. The study was done through a self-administered questionnaire survey participated by 286 undergraduates. The results revealed that undergraduates choosing for conventional banks considered convenience as the main factor. Meanwhile, religiosity and technology were considered as the most important factors for the other two groups of undergraduates respectively. In addition, this study also indicated that undergraduates were not homogeneous in regard to bank patronization. In short, as undergraduates opting for different type of banks employed different selection criteria, bank operators are urged to understand their target customers well before they start to invest in marketing programs.